Smart Card Research and Advanced Applications - Grimaud, Gilles (Springer, 2017)
This book constitutes the refereed proceedings of the 8th International Conference on Smart Card Research and Advanced Applications, CARDIS 2008, held in London, UK, in September 2008. The 21 revised full papers presented, together with the abstract of one invited talk, were carefully reviewed and selected from 51 submissions. The papers deal with the various issues related to the use of small electronic tokens in the process of human-machine interactions. The conference scopes include numerous subfields such as networking, efficient implementations, physical security, biometrics, etc.